2019
DOI: 10.1002/aorn.12616
|View full text |Cite
|
Sign up to set email alerts
|

Debriefing in the OR: A Quality Improvement Project

Abstract: Ineffective communication can contribute to perioperative adverse events even when a safety checklist is used. The purpose of this project was to improve the overall debriefing process of the surgical safety checklist. We included coaches and used the International Classification for Patient Safety for categorizing any opportunities for improvement that were identified during the debriefing process. The results of our project showed an increase in both the total number of debriefings completed and the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…In a second study, two coaches met with nurses and surgeons either as a group or individually. The researchers found an increase in the number of debriefs performed and the completeness of debriefs after coaching [26]. These authors also found auditing an important part of their implementation project [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a second study, two coaches met with nurses and surgeons either as a group or individually. The researchers found an increase in the number of debriefs performed and the completeness of debriefs after coaching [26]. These authors also found auditing an important part of their implementation project [26].…”
Section: Resultsmentioning
confidence: 99%
“…The researchers found an increase in the number of debriefs performed and the completeness of debriefs after coaching [26]. These authors also found auditing an important part of their implementation project [26]. In a third study, the researchers gave surgeons structured feedback on the quality of their debriefs and provided one-on-one coaching for surgeons who were finding debriefing difficult.…”
Section: Resultsmentioning
confidence: 99%
“…This study adds to the existing evidence that quality improvement initiatives centered around auditing and coaching surgical personnel can lead to improvements in surgical safety practices, specifically compliance with and quality of surgical debriefs. 37,38 However, this study is unique in that it examined debrief performance longitudinally and assessed for sustained improvements, rather than simply evaluating performance before versus after implementation of a quality initiative. One advantage of this study is that the initiative simply involved evaluating surgical cases with a structured form and periodically reporting debrief performance to the surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Open-ended questions require qualitative information gathered through focused discussion, which can reduce team member engagement. 10 Questions such as “ What are the key concerns for this patient’s recovery and management?” might be replaced with “Are there any concerns for recovery?,” which elicits a yes or no response but still captures the important safety data.…”
mentioning
confidence: 99%